Work-life balance and job satisfaction of Chinese nurses during the COVID-19 pandemic - PENG, Lin (2022)
Abstract Since the outbreak of the COVID-19 pandemic, global health, economies, environments, and societies have been affected by the epidemic. As front-line nursing workers in epidemic prevention and control, nurses have faced severe challenges as their work hours and workload have increased, and they need to adapt to new epidemic changes constantly. Work-life balance is one of the topics of concern in society, and job satisfaction is essential to the development of the healthcare industry. However, work pressure and day and night shifts may cause nurses stress and anxiety, affecting their work-life balance and job satisfaction. Based on this background, this study aims to examine Chinese nurses' work-life balance and job satisfaction during the COVID-19 pandemic and determine the relationship between work-life balance and job satisfaction. This study used a quantitative research method to collect data from 331 nurses in a Chinese hospital through an online questionnaire. The study's findings showed that Chinese nurses had a low level of work-life balance and that work-life balance had a significant positive effect on job satisfaction. In addition, COVID-19 had a negative impact on nurses' work-life balance. This study proposes some practical recommendations to improve the work-life balance of nurses and enhance job satisfaction.